Opinion 2449: Anolis chlorocyanus Duméril & Bibron, 1837 and Anolis coelestinus Cope, 1862 (Reptilia, Squamata): conservation of usage of specific names by designation of a neotype for the former species not approved - ICZN (Bulletin of Zoological Nomenclature, 2020)
he International Commission on Zoological Nomenclature has declined to use its plenary power to designate a neotype for Anolis chlorocyanus Duméril & Bibron, 1837. As a result, the specific name Anolis chlorocyanus Duméril & Bibron, 1837, will have priority over A. coelestinus Cope, 1862 as the valid name for the well-known, predominantly North Island Hispaniolan anole species. The species known as Anolis chlorocyanus since Dunn (1930) needs to be renamed.
Keywords: Nomenclature; taxonomy; Reptilia; Squamata; Dactyloidae; Anolis; Anolis chlorocyanus; Anolis coelestinus; Hispaniolan green anoles; Greater Antilles; Hispaniola